Public sociology : fifteen eminent sociologists debate politics and the profession in the twenty-first century - Clawson, Dan (University of California Press, 2007)
In 2004, Michael Burawoy, speaking as president of the American Sociological Association, generated far-reaching controversy when he issued an ambitious and impassioned call for a "public sociology." Burawoy argued that sociology should speak beyond the university. This volume debates the perils and the potentials of Burawoy's challenge